Analyzing the influence of urban vegetation cover on land surface temperature in Southwestern Nigeria - Aladesanmi Daniel Agbelade (Discover Environment)
Abstract Urbanization and the expansion of urban infrastructure have led to the development of new land use policies that impact biodiversity and ecosystem services in Nigeria’s rapidly growing cities. Key drivers of this urbanization include population pressure, infrastructure development, rural-to-urban migration, and economic growth. This study investigates the effect of urban vegetation cover on land surface temperature in southwestern Nigeria, using the spectral radiance method, the support vector machine (SVM) algorithm and the normalized difference vegetation index (NDVI). This study analyzed remote sensing data to classify land use changes from 1991 to 2021 based on lithological characteristics. Additionally, the urban vegetation covers (VC) of the two urban centres were assessed through NDVI analysis. The highest NDVI values was recorded in Akure 0.358 to 0.394, and Osogbo had 0.449 to 0.464 while the lowest for Akure − 0.052 to 0.005 and Osogbo had − 0.058 to − 0.009. The analysis of urban land surface temperatures from 1991 to 2021 indicated maximum temperatures of 29.53 to 34.22 °C in Akure and 31.11 to 36.85 °C in Osogbo, with minimum temperatures of 18.22 to 22.48 °C in Akure and 21.72 to 23.66 °C in Osogbo. Primarily, urban land surface temperatures have steadily increased in both cities due to deforestation and urban infrastructural development which have diminished vegetation cover. This research highlights the need for urban green infrastructure and effective planning strategies to mitigate the impacts of rising land surface temperatures.